Utility and ruin probability relationship through premium equivalence (UP Los Baños Journal, 2015)
Utility is a satisfaction received from consuming a commodity or service. Ruin probability is the probability that an insurer's surplus will fall below zero for a certain period of time. While many researches have focused on the pricing of insurance premium using the concept of utility functions some have focused on finding the probability that the company or insurer will be insolvent at any given point via the ruin probability. This paper focused mainly on the calculation of the insurance premium by setting a tolerance level for the ruin probability. After the premium was solved, the corresponding utility was determined.